A STUDY OF THE APPLICATION AND IMPACT OF CROSS-CULTURAL NARRATIVE IN FILM AND TELEVISION ANIMATION - Long Feng; Wan Aida Wan Yahaya (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In the context of globalization, the creation of film and animation is experiencing the transformation of narrative paradigm, and cross-cultural narrative, as a creative practice of cultural communication, is reshaping the value transmission path of cultural products. Currently, the film and animation industry is facing a double challenge: breaking through cultural barriers to realize diversified expression, and building a mechanism for cross-cultural audience identification. By constructing the analytical framework of “narrative elements - cultural mapping - market response”, this study provides in-depth interpretation of typical texts such as “Coco”, “Zootopia” and “Mulan” from the three dimensions of semiotic decoding of roles, spatial-temporal reconstruction of narrative and translation of visual symbols. It is found that successful cross-cultural narratives follow the triple conversion mechanism of “cultural anchor point-universal value-innovative expression”, and in the cases of Coco, a cultural reconstruction of the Mexican Day of the Dead, and Zootopia, a metaphor of multiple civilizations in the animal city-state, the organic grafting of local cultural elements with global aesthetic paradigms is realized. This narrative strategy not only enhances the cultural discount rate of the works, but also creates the value-added effect of cultural capital, providing methodological inspiration for the globalization of the film and animation industry.